Optimization of Claudin-5 and ICAM-1 protein detection by using capillary-based immunoassay method in human brain endothelial cells - Jufri, Nurul Farhana; Salyam, Tharsini; Ibrahim, Farah Wahida; Abdul Latif, Mazlyzam; Hamid, Asmah (Life Sciences, Medicine and Biomedicine, 2021)
Background: Human brain endothelial cells (HBECs) are part of the blood-brain barrier (BBB). BBB acts as a barrier to control the passage of molecules or materials from the blood into the brain. Identification of specific proteins changes in their expressions that are related to disease state is important in order to understand the disease mechanism involving brain vasculature. To achieve that, the techniques involve in identifying the proteins of interest must be optimized prior to further investigation. Methodology: In this study, identification of Claudin-5 in HBEC lysates was tested using different sample preparation techniques such as; 1) reducing with Dithiothreitol (DTT) and non-reducing conditions; 2) denaturing by heating at 95°C for 5 minutes or 70°C for 20 minutes and 3) protein loading at 3 and 4 µg. The samples were then subjected to an automated capillary-based immunoassay, Jess. Results and Discussion: The results showed that HBEC samples loaded at 4 µg and heated for 5 minutes at 95°C with DTT produced clearer and intense bands for Claudin-5 identification compared to the other set ups. As reducing condition and denaturing by heated at 95°C for 5 minutes conditions demonstrated good results, the conditions were used to identify ICAM-1 expression at different protein loading (3 and 4 µg). The result demonstrated that HBEC samples heated for 5 minutes at 95°C with DTT and loaded at 4 µg produced a good detection for ICAM-1. Conclusion: These optimized conditions could be served as a standard procedure for further identification of Claudin-5 and ICAM-1 proteins in HBEC using a capillary immunoassay instrument.